A human case study demonstrating the safety and effectiveness of laparoscopic surgical glue injection hernioplasty for pediatric indirect inguinal hernia - Si Min Park; Young Ju Hong; Eun Young Chang; Seok Joo Han (Journal of Pediatric Surgery Case Reports, 2014)
The purpose of this pediatric case report was to provide clinical evidence supporting the safety and effectiveness of laparoscopic surgical glue injection hernioplasty (LSGIH) in humans for indirect inguinal hernia repair. We performed LSGIH on a female newborn for a right indirect inguinal hernia that was incidentally discovered during a laparoscopic right salphingo-oophorectomy for prenatal right ovarian cyst torsion. Under laparoscopic control, the internal ring was closed by injection of Histoacryl® into the internal opening of the patent processus vaginalis. One month later, the patient underwent another laparoscopic operation due to torsion of a newly developed contralateral ovarian cyst. During the second operation, we were able to clearly observe the previous LSGIH site. Despite partial absorption of the injected Histoacryl®, the opening of the internal ring remained closed without any evidence of adhesions. This case supports LSGIH as a simple, safe, and useful technique for pediatric inguinal hernioplasty. However, more clinical trials should be performed to confirm the long-term reliability and safety of LSGIH in humans.